Challenging the Perception: Turning the Ideal into Reality - Horton, Gail (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Most initiatives in many UK universities designed to integrate their home and international student cohorts are likely to take place either within academic courses or through extra-curricular activities. Unusually, for 8 years between the academic years 2007/8 and 2014/15, the University of Birmingham in the UK ran an elective module within its Personal Skills Award (PSA) that combined academic assessed learning in a social setting. This module sought to facilitate intercultural communication using the potential of its culturally diverse student population as a resource for intercultural learning in order to realise De Vita’s (2005) ‘ideal’. The participants, home and international undergraduates, developed their intercultural awareness over a period of several weeks by being each other’s cultural informants in social meetings outside the classroom, acting in effect as case studies. To pass the module and achieve 10 credits (which were included on their degree transcript) the participants had to submit a reflective learning journal and attend a short interview about what they had learnt. Data obtained from responses to a questionnaire sent to course participants concludes that they benefitted from, and valued, not only the autonomous dual learner-teacher approach but also the informal nature of the learning situation .